Strategies for Awareness and Implementation of Adventist Financial Management Software in Local Churches in Madagascar - Rolland Eugene Ralandison; Saban Gracel Salangsang (Bisnis, Jasa dan Keuangan, 2026)
This study aims to examine strategies for awareness and implementation of Adventist Financial Management Software in local churches in Madagascar. Using a qualitative approach, the study collected data from 30 participants, including church treasurers, pastors, conference financial officers, IT personnel, and church members, through semi-structured interviews and document analysis. The findings reveal varying levels of awareness, with higher understanding among financial officers and lower awareness among general members, highlighting the importance of structured communication and training. The study also finds that the software contributes significantly to improving financial transparency, accountability, reporting accuracy, and operational efficiency. However, several challenges affect implementation, including limited technical capacity, inadequate infrastructure, resistance to change, insufficient training, and inconsistent leadership support. The results further indicate that leadership engagement and organizational support are critical in driving system adoption, while continuous training and capacity building enhance user competence and system sustainability. Effective strategies such as context-sensitive awareness programs, stakeholder involvement, integration into organizational processes, and ongoing monitoring are essential for successful implementation. The study concludes that while financial management software has strong potential to modernize church financial practices, its success depends on aligning technological, organizational, and human factors. It recommends strengthening training initiatives, enhancing leadership commitment, and improving infrastructure support. Future research should explore quantitative evaluations and comparative studies to further understand technology adoption in faith-based organizations.